Tajikistan : a political and social history - Nourzhanov, Kirill; Bleuer, Christian (Asian studies series., 2013)
This book is a historical study of the Tajiks in Central Asia from the ancient times to the post-Soviet period. For millennia, these descendants of the original Aryan settlers were part of many different empires set up by Greek, Arab, Turkic and Russian invaders, as well as their own, most notably during the Middle Ages. The emergence of the modern state of Tajikistan began after 1917 under Soviet rule, and culminated in the promulgation of independence from the moribund USSR in 1991. In the subsequent civil war that raged between 1992 and 1997, Tajikistan came close to becoming a failed state. The legacy of that internal conflict remains critical to understanding politics in Tajikistan a generation later. Exploring the patterns of ethnic identity and the exigencies of state formation, the book argues that despite a strong sense of belonging underpinned by shared history, mythology and cultural traits, the Tajiks have not succeeded in forming a consolidated nation. The politics of the Russian colonial administration, the national-territorial delimitation under Stalin, and the Soviet strategy of socio-economic modernisation contributed to the preservation and reification of sub-ethnic cleavages and regional identities. The book demonstrates the impact of region-based elite clans on Tajikistan's political trajectory in the twilight years of the Soviet era, and identifies objective and subjective factors that led to the civil war. It concludes with a survey of the process of national reconciliation after 1997, and the formal and informal political actors, including Islamist groups, who compete for influence in Tajik society.